2019
DOI: 10.1136/neurintsurg-2018-014403
|View full text |Cite
|
Sign up to set email alerts
|

SEIMLESS: Simultaneous Extracranial, Intracranial Management of (tandem) LESsions in Stroke

Abstract: BackgroundPooled individual data from the landmark stroke trials of 2015 conclude that the benefit of endovascular thrombectomy for patients with intracranial arterial occlusion also extends to patients with concomitant (so-called ’tandem') occlusions of proximal vessels. However, there is heterogeneity and debate in the management of these patients, without a clear standard of care. In particular, there is contention regarding whether the proximal or distal lesion should be treated first. We present a case co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…Both the very high rates of successfully reperfused patients and the short groin to reperfusion times in this study translated into a rate of 48% favorable outcome at discharge and an even higher rate of 55% at 90 days, which is consistent with what has been reported in the literature for the outcome after interventional treatment of AIS caused by TO with rates ranging from 28-60% [4,7,12,13]. A recent case series demonstrated advantages of a simultaneous treatment of proximal ICA lesions with balloon angioplasty in a TO situation; however, only five patients were included and carotid stenting was avoided [15].…”
Section: Discussionsupporting
confidence: 88%
“…Both the very high rates of successfully reperfused patients and the short groin to reperfusion times in this study translated into a rate of 48% favorable outcome at discharge and an even higher rate of 55% at 90 days, which is consistent with what has been reported in the literature for the outcome after interventional treatment of AIS caused by TO with rates ranging from 28-60% [4,7,12,13]. A recent case series demonstrated advantages of a simultaneous treatment of proximal ICA lesions with balloon angioplasty in a TO situation; however, only five patients were included and carotid stenting was avoided [15].…”
Section: Discussionsupporting
confidence: 88%
“…Sultan-Qurraie et al describe a similar technique for the treatment of concomitant carotid and intracranial large vessel occlusions 15 although there are some important distinctions to be made between these two techniques. First of all, their SEIMLesS technique recommends advancing the BCG as distally as possible, but it is not reported whether they attempted or were successful in their five-patient retrospective group.…”
Section: Discussionmentioning
confidence: 99%
“…A large prospective study demonstrates that identification of a tandem lesion independently predicts poor response to rt-PA in terms of recanalization (38)(39)(40). While platelet activation is accelerated at the site of ruptured atherosclerotic plaque (18,38), the lack of effect of rt-PA could be related to the fact that most tandem lesions were secondary to atherothrombotic disease of the carotid artery with large clot burden, which is a known predictor of poor recanalization after rt-PA (41)(42)(43). Kim et al supposed that the low recanalization rate may be attributed to the large amount of thrombus (44).…”
Section: Figure 4 |mentioning
confidence: 99%
“…In terms of carotid atherothrombosis, the presence of a distal MCA occlusion usually is associated to an artery to artery embolism, with a clot proceeding from the carotid plaque which was platelet-rich lyticresistant (41). Despite this, Ali et al confirmed that 30% of the tandem -PAlesions achieved good outcome treated with rt-PA. AIS with tandem lesions should not be used as an exclusion from standard rt-PA therapy within the therapeutic window (18).…”
Section: Figure 4 |mentioning
confidence: 99%
See 1 more Smart Citation